Recurrent and Metastatic Cutaneous Squamous Cell Carcinomas in a Cohort of 774 Patients in Finland - Niina Korhonen; Leea Ylitalo; Tiina Luukkaala; Julius Itkonen; Henni Häihälä; Juha Jernman; Erna Snellman; Johanna Palve (Medical Journals Sweden, 2020)
Recognising patients with high risk cutaneous squamous cell carcinomas is essential in planning effective monitoring. The aim of this study was to determine the rate of local recurrences and metastases of cutaneous squamous cell carcinomas in a previously defined patient cohort in Finland. Pathology database search was performed to identify cutaneous squamous cell carcinoma patients and their medical records were reviewed. The cohort consisted of 774 patients with 1,131 cutaneous squamous cell carcinoma tumours. Overall, 4.2% (48/1,131) of the tumours were metastatic and 2.2% (25/1,131) had a local recurrence. Three of the metastatic tumours and 8 of the recurrent tumours had an invasion depth of ≤ 2 mm. The majority of metastases (28/48; 58%) were found within 3 months of the diagnosis of cutaneous squamous cell carcinoma. In conclusion, our study demonstrated recurrences and metastases even in the case of thin cutaneous squamous cell carcinomas and in high-risk cases close monitoring should be organised during the first years after diagnosis.